Conjugate Mates For Non-Null Frenet Curves - Kelleci, Alev (My University, 2019)
For each non-null Frenet curve ?? in Minkowski 3-space, there exists a unique unit speed non-null curve ??? tangent tothe principal binormal vector field of ??. We briefly call this curve ??? the conjugate mate of ??. The aim of this paperis to prove some relationships between a non-null Frenet curve and its non-null conjugate mate.
Keywords: Matematik; Fizik; Matematik